The Effects of Monetary and Fiscal Policy on Aggregate Demand in a Small Open Economy : An Application of the Structural Error Correction Model - Konuki, Tetsuya (IMF Working Papers; Working Paper, 2000)
This paper empirically analyzes the short-run effects of monetary and fiscal policy on aggregate demand, using the two-step structural error correction method. This method has an advantage over the standard reduced-form error correction method in providing a meaningful interpretation for impulse responses. The results are in sharp contrast to those of the traditional Mundell-Fleming and Dornbusch models: after the monetary (fiscal) policy is relaxed, the home currency depreciates (appreciates) for a substantial period of time, and the aggregate demand first expands (contracts) then gradually returns toward its original path.